2013
DOI: 10.1007/s10661-013-3101-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of aerosol species, trace gasses, and meteorology in Chicago

Abstract: Both canonical correlation analysis (CCA) and principal component analysis (PCA) were applied to atmospheric aerosol and trace gas concentrations and meteorological data collected in Chicago during the summer months of 2002, 2003, and 2004. Concentrations of ammonium, calcium, nitrate, sulfate, and oxalate particulate matter, as well as, meteorological parameters temperature, wind speed, wind direction, and humidity were subjected to CCA and PCA. Ozone and nitrogen oxide mixing ratios were also included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
2
11
0
1
Order By: Relevance
“…Equilibrium is shifted from ammonium nitrate to gaseous nitric acid and ammonia in this case (Finlayson-Pitts and Pitts 2000). A similar result to PC1 was found when applying multivariate statistics to summer 2002-2004 data taken at the same location (Binaku et al 2013). Binaku et al (2013) suggested that organonitrate compounds play a role in the atmospheric signature of nitrate in Chicago.…”
Section: Principal Component Analysissupporting
confidence: 71%
See 3 more Smart Citations
“…Equilibrium is shifted from ammonium nitrate to gaseous nitric acid and ammonia in this case (Finlayson-Pitts and Pitts 2000). A similar result to PC1 was found when applying multivariate statistics to summer 2002-2004 data taken at the same location (Binaku et al 2013). Binaku et al (2013) suggested that organonitrate compounds play a role in the atmospheric signature of nitrate in Chicago.…”
Section: Principal Component Analysissupporting
confidence: 71%
“…A similar result to PC1 was found when applying multivariate statistics to summer 2002-2004 data taken at the same location (Binaku et al 2013). Binaku et al (2013) suggested that organonitrate compounds play a role in the atmospheric signature of nitrate in Chicago. Many urban studies have measured organonitrate compounds in the organic aerosol fraction.…”
Section: Principal Component Analysissupporting
confidence: 71%
See 2 more Smart Citations
“…Major point sources of particulate air pollution include 2 coal-fired power plants and metal processing, paint, and solvent factories (the last being in the southern and southeast parts of the city) (67). Mobile source emissions account for a majority of atmospheric nitrogen compounds, while refineries, coal burning, and steel manufacturing are responsible for sulfur compounds (67). The composition of airborne PM is primarily sulfate and organic carbons and secondary nitrates (68).…”
Section: Exposure Of Mice To Pmmentioning
confidence: 99%